Subjective health perception in healthy young men changes in response to experimentally restricted sleep and subsequent recovery sleep - Lekander, Mats; Andreasson, Anna Nixon; Kecklund, Göran; Ekman, Rolf; Ingre, Michael; Akerstedt, Torbjorn; Axelsson, John (Brain, behavior, and immunity, 2013)
•Subjective health was compromised through experimental sleep restriction, an effect associated with increased fatigue but not IL-1 or TNF-alpha. Sleep and subjective health are both prospectively related to objective indices of health and health care use. Here, we tested whether five days with restricted sleep and subsequent recovery days affect subjective health and is related to increased levels of circulating IL-6 and TNF-α and fatigue. Nine healthy men (23–28years) went through a 6-week sleep protocol with subjects as their own controls in a repeated measures design with a total of 11 nights in a sleep laboratory. The experimental part of the protocol included three baseline days (sleep 23–07h), five days with sleep restriction (03–07h) and three recovery days (23–07h) in the sleep laboratory. Subjective health and fatigue was recorded daily. Eight blood samples were drawn each day (every third hour) on 8days of the protocol and analyzed with respect to IL-6 and TNF-α. Subjective health deteriorated gradually during restricted sleep (p=.002) and returned to baseline levels after three days of recovery. IL-6 and TNF-α did not change significantly. Fatigue increased gradually during sleep restriction (p=.001), which significantly contributed to the association between restricted sleep and subjective health. The study is the first to show that subjective health is directly responsive to changes in sleep length and related to increased fatigue. Thus, subjective health is differently appraised after manipulation of one of its presumed determinants. Larger experimental studies would be beneficial to further distinguish causation from association regarding the underpinnings of subjective health.